A diver operated stereo-video approach for characterizing reef fish spawning aggregations: The Galapagos Marine Reserve as case study. (30th September 2020) - Rastoin-Laplane, Etienne; Goetze, Jordan; Harvey, Euan S.; Acuña-Marrero, David; Fernique, Pierre; Salinas-de-León, Pelayo
Abstract: The alarming decline of spawning aggregations across the world highlights the need to improve their long-term monitoring and protection. Here, we examined the ability of diver operated stereo-video to characterize reef fish spawning aggregations, using an opportunistic encounter with the first spawning aggregation of the Mexican hogfish, Bodianus diplotaenia, recorded in the Galapagos Marine Reserve. We aimed to provide estimates of total density, length and reproductive behaviour, using quantitative surveys and 3D representation of the spawning event. 3D scenes of aggregating fish in relation to reef substrate were produced to compute distances between individuals (of the same and different sex), and between individuals and the substrate. Males swam significantly higher in the water column and further away from each other when compared to females, which displayed sociable behaviour closer to the bottom. The mean fork length of males (39.79 ± 6.98 cm) was nearly twice the size of females (24.14 ± 5.39 cm). We show that diver operated stereo-video can provide accurate baseline measures of fish length, density and reproductive behaviours. Our study offers a new method to characterize fish mating systems, and contributes to expanding the range of easily repeatable low-impact tools for the long-term monitoring of spawning events. Highlights: First documented report of an aggregation of Bodianus diploaenia in the Galapagos. New method to conduct 3D characterizations of aggregations using stereo-video. We provide accurate length-frequency distributions of the aggregating fish. Stereo-video presents great potential for the long-term monitoring of spawning. Stereo-video is an effective tool for the study of fish mating behaviours.